X-Band Waveguide Reflectionless Filtering Antenna Array With High Selectivity - Jun Ma; Fuchang Chen; Kairan Xiang (IEEE Open Journal of Antennas and Propagation)
In this paper, a waveguide reflectionless filtering antenna array with high selectivity is proposed. Instead of reflecting the out-of-band signal back to the source, the proposed antenna array dissipates the energy through a lossy network, which can reduce the interference to the former stage. The prototype circuit of the reflectionless filtering antenna array based on the complementary duplex theory is established, consisting of a bandpass network and a bandstop network, whose responses are completely complementary. High selectivity is achieved by introducing non-resonating nodes (NRNs) and configuring the transmission zeros (TZs) of the bandpass network and the reflection zeros (RZs) of the bandstop network to be set at the same frequency. The synthesis of the prototype circuit is given and a fourth-order reflectionless filtering antenna array is designed and fabricated to verify the design method. Two TZs are generated at 9.62 GHz and 10.4 GHz, leading to an out-of-band suppression of more than 23 dB. The measured $|S_{11}|$ is less than −10 dB from 8.3 GHz to 12 GHz, providing a wideband reflectionless filtering response with high selectivity and high gain.